2018
DOI: 10.3389/fnagi.2017.00440
|View full text |Cite
|
Sign up to set email alerts
|

[18F]-THK5351 PET Correlates with Topology and Symptom Severity in Progressive Supranuclear Palsy

Abstract: Progressive supranuclear palsy (PSP) is a neurodegenerative movement disorder characterized by deposition of fibrillar aggregates of 4R tau-protein in neurons and glial cells of the brain. These deposits are a key neuropathological finding, allowing a diagnosis of “definite PSP,” which is usually established post mortem. To date criteria for clinical diagnosis of PSP in vivo do not include biomarkers of tau pathology. For intervention trials, it is increasingly important to (i) establish biomarkers for an earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 45 publications
2
62
2
Order By: Relevance
“…7,8 Tau PET studies have suggested potential retention topography differences for PSP and CBD using tracers (e.g., first-generation compounds like 18 F-AV-1451 and 18 F-THK5351; second-generation compounds like 18 F-PI2620) not specific for 4R tau pathology 9 and/or with off-target binding in the midbrain and basal ganglia. 10 Postmortem studies with in vivo tau PET have rather small samples and conflicting results, with some reporting high 9,11 and some reporting no association between the tracer retention and postmortem tau burden in PSP and CBD. 10,12,13 Overall, future studies are required to determine whether tau PET can be a reliable method for differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Tau PET studies have suggested potential retention topography differences for PSP and CBD using tracers (e.g., first-generation compounds like 18 F-AV-1451 and 18 F-THK5351; second-generation compounds like 18 F-PI2620) not specific for 4R tau pathology 9 and/or with off-target binding in the midbrain and basal ganglia. 10 Postmortem studies with in vivo tau PET have rather small samples and conflicting results, with some reporting high 9,11 and some reporting no association between the tracer retention and postmortem tau burden in PSP and CBD. 10,12,13 Overall, future studies are required to determine whether tau PET can be a reliable method for differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The first generation of tau‐radioligands (18F‐AV1451, 18F‐THK5351, and 11C‐PBB3) have been assessed in small PSP cohorts. Their distribution in the brain broadly corresponds with the areas expected to be affected by PSP pathology, and this has been reported for different PSP phenotypes . Most studies have demonstrated group differences in radioligand uptake between PSP patients and controls in the basal ganglia, STN, thalamus, dentate nucleus, and midbrain .…”
Section: Psp: Milestones Of the Recent 10 Yearsmentioning
confidence: 60%
“…Their distribution in the brain broadly corresponds with the areas expected to be affected by PSP pathology, and this has been reported for different PSP phenotypes. [69][70][71] Most studies have demonstrated group differences in radioligand uptake between PSP patients and controls in the basal ganglia, STN, thalamus, dentate nucleus, and midbrain. [69][70][71] Correlations between the degree of radioligand uptake and severity of clinical symptoms have also been reported, albeit not consistently.…”
Section: Neuroimaging In Pspmentioning
confidence: 99%
See 2 more Smart Citations